2018
DOI: 10.19044/esj.2018.v14n33p267
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation Des Pratiques Phytosanitaires Paysannes Dans Les Vergers De Cacao Dans Le Departement De Daloa, Côte d’Ivoire

Abstract: This paper focuses on identifying pesticides uses in the protection of cocoa tree. To do this, a survey was conducted among 129 randomly selected cocoa producers in the Daloa zone in Côte d'Ivoire. The results showed that 79.84% of the producers interviewed, use pesticides. Twenty-seven (27) pesticides were identified; among them, 24 were insecticides, 3 were fungicides, and two were not licensed. More than 50% of the insecticides used by famers were neonicotinoids combined with pyrethroids. None of the pestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
1
0
Order By: Relevance
“…This study also reveals that chemical insecticides are used by a very large number of cocoa farmers in the Méagui localities where the survey was conducted. This result agrees with the results of Siapo et al [38] and Ano et al [42] who noted in some localities of Daloa and Abengourou, high proportions of cocoa farmers who use chemical pest control in cocoa farms. This does not seem to be the case in other localities of Abengourou, Divo, and Soubré where Koua et al [15] noted a low proportion of cocoa farmers who treat their plantations with insecticides.…”
Section: Discussionsupporting
confidence: 93%
“…This study also reveals that chemical insecticides are used by a very large number of cocoa farmers in the Méagui localities where the survey was conducted. This result agrees with the results of Siapo et al [38] and Ano et al [42] who noted in some localities of Daloa and Abengourou, high proportions of cocoa farmers who use chemical pest control in cocoa farms. This does not seem to be the case in other localities of Abengourou, Divo, and Soubré where Koua et al [15] noted a low proportion of cocoa farmers who treat their plantations with insecticides.…”
Section: Discussionsupporting
confidence: 93%
“…The Haut-Sassandra region, one of the main cocoa production areas in Côte d'Ivoire, is no exception to that key issue. Previous studies by N'Guessan et al (2014) [14] ; Kouamé et al (2015) [15] and Siapo et al (2018) [16] have reported the importance of pests in this region. In such a context, understanding the perception and knowledge that local farmers have of the various threats and the practices implemented to address them.…”
Section: Introductionmentioning
confidence: 73%
“…This low level of innovation adoption may be related in part to the low income level of producers, as well as the lack of information [22] . Siapo et al (2018) [16] argued that the cost of seeds in the department of Daloa is 17 USD / ha for "Mercedes cocoa" while the producer pays nothing for the "all coming". The free "all coming" plant material would therefore be an important factor in the choice of plant material in the area of study.…”
Section: Discussionmentioning
confidence: 99%
“…Available studies and scientific resources , which works, amongst others, in quality control of agrochemicals and feeds, conducts research on pesticide and mycotoxin residues in agri-food products, and provides development research and consulting. There has been considerable work on mosquitoes and their resistance to pesticides and study of neonicotinoids effects in freshwater fish, and a study evaluating cocoa farmers' phytosanitary practices (Martin et al, 2018).…”
Section: Feedback From West African Countriesmentioning
confidence: 99%